ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PPh PASAL 21 PADA GAJI KARYAWAN PT. TANAKA MEDAN SAKTI - Pratiwi, Anggi; Zahari, Zahari; Nurhayati, Nurhayati (Worksheet : Jurnal Akuntansi, 2024)
PT. Tanaka Medan Sakti is a company that operates in the electronic field that distributes its goods to stores in the field as well as outside the field area. This research aims to find out how and the system in the calculation and reporting of Income Tax (PPh) Article 21 on the salary of employees at PT. Tanaka Sakti Field. The data analysis techniques used are qualitative descriptive and the techniques used in data collection are using primary and secondary data. PT Tanaka Medan Sakti has carried out the calculation and reporting of Article 21 Income Tax (PPh) which has been in accordance with the Working Law and Regulations in force in Indonesia. In addition, the company also does not grant a fine to permanent employees who do not have a compulsory tax number (NPWP), because according to the Act No. 36 of 2008 paragraph 5 (a) stated that the size of the rate imposed on the taxable person who does not possess the NPWPs at all, they pay their tax higher than 20% (twenty percent) of the tax rate established on the employee who has the compulsor tax number. (NPWP). The results of this research are on the reporting and calculation of PPh Article 21 on the salary of employees at PT. Tanaka Sakti Field has been in accordance with the rules of employment already regulated. As for the analysis of the calculation of the salary of a fixed employee, the Sakti fields are salaries received by every employee paid to the company on the 28th of each month. Likewise, the net salary received by the employee in the Sakti field is the aggregate salary, plus the benefits and minus the pension benefits and the old-day guarantee benefits that are cut off every month against the salary.